Anemia Gravis Caused by Chronic Multiple Infection of Helminthiasis on Geriatric: An Evidence-Based Case Report - Trasia, Reqgi First; Dua, Muhammad Yugo Hario Sakti; Desyana, Rizqia Meta Fairuz; Akmaluddin, Muhammad; Kamila, Muthia Dwifitri (UNUSA Press, 2025)
Introduction: Soil-transmitted helminth (STH) infections remain the most prevalent parasitic diseases globally. In elderly individuals, such infections can lead to significant morbidity, including anemia, fatigue, decreased activity levels, cognitive impairment, nutritional deficiencies, and gastrointestinal disturbances. This case report aims to highlight a rare instance of severe anemia caused by worm infestation in an elderly patient. Case: A 57-year-old male presented with a 7-day history of fatigue, dizziness, and marked pallor, accompanied by worsening abdominal pain over the past 5 days. Physical examination revealed moderate illness with pale conjunctiva, a mildly distended abdomen, and hyperactive bowel sounds. Laboratory tests showed a significant drop in hemoglobin, hematocrit, erythrocyte count, serum iron, TIBC, and ferritin levels. Endoscopic evaluation revealed esophagitis, a Forrest III gastric ulcer, and multiple worms in the duodenum, later identified macroscopically as Ascaris lumbricoides. Discussion: Worm infection is the most recent known diagnosis. The patient has undergone a complete stool analysis, but no worm eggs were found microscopically. This condition is very likely a false negative due to various factors, such as a less fresh stool sample (not examined immediately within 30 minutes) and human error by the analyst. The diagnosis was made after an endoscopic examination and multiple worms were found in the duodenum. When viewed from the large number of worms, it is likely that the patient has a severe and chronic worm infection. This is what causes the patient to suffer from anemia gravis with Hb 5.9. Conclusions: Initial clinical and laboratory assessments led to a diagnosis of anemia gravis. The patient received three units of packed red cells. Further investigations confirmed microcytic hypochromic anemia due to iron deficiency and chronic inflammation, with parasitic infection as the underlying cause. Treatment with a single 400 mg dose of albendazole resulted in clinical improvement, allowing for safe discharge.